Organizational Commitment as Mediating Variable of Employee Job Satisfaction Toward Turnover Intentions - Fathul Bachri; Nihayatu Aslamatis Solekah (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2021)
The high employees turnover at PT. BRI Syariah shows low job satisfaction and organizational commitment and high desire to change jobs. The purpose of this study was to determine the effect of job satisfaction and organizational commitment on turnover intentions directly or indirectly. Quantitative methods are used in this study. The population is employees at PT. BRI Syariah of Malang Branch with 50 people. The sampling technique used was census sampling with sample size of 50 people. Data collection techniques using questionnaires and path analysis. The results of the study indicated that there is negative and significant effect of job satisfaction on turnover intentions, positive and significant effect of job satisfaction on organizational commitment, negative and significant effect of organizational commitment on turnover intentions, and negative and significant effect of job satisfaction on turnover intentions indirectly through organizational commitment.